Ideal Cardiovascular Health and Cognitive Aging in the Northern Manhattan Study. Issue 3 (March 2016) - Gardener, Hannah; Wright, Clinton B.; Dong, Chuanhui; Cheung, Ken; DeRosa, Janet; Nannery, Micaela; Stern, Yaakov; Elkind, Mitchell S. V.; Sacco, Ralph L.
Abstract : Background: The American Heart Association defined target levels for 7 cardiovascular health (CVH) factors: smoking, body mass index, physical activity, diet, blood pressure, cholesterol, and glucose. We hypothesized that a greater number of American Heart Association ideal CVH metrics would be associated with less decline in cognitive performance in our multiethnic population. Methods and Results: A subsample from the population‐based Northern Manhattan Study underwent repeated neuropsychological testing (mean interval 6±2 years). Domain‐specific Z scores were derived by using factor analysis for the domains of Episodic Memory, Semantic Memory, Executive Function, and Processing Speed, based on initial performance and decline over time. Linear regression models were constructed to examine the relationship between the number of ideal CVH metrics at enrollment with later cognitive performance and decline, adjusting for sociodemographics and magnetic resonance imaging brain markers. Among 1033 participants (mean age at initial cognitive assessment 72±8 years, 39% male, 19% black, 16% white, 65% Hispanic; n=722 with repeat testing), 3% had 0 ideal factors, 15% had 1 factor, 33% had 2 factors, 30% had 3 factors, 14% had 4 factors, 4% had 5 factors, 1% had 6 factors, and 0% had 7 factors. An increasing number of ideal CVH factors was associated with better processing speed at initial assessment and less decline. The association was driven by nonsmoking and glucose. Among those with better cognitive performance at initial assessment, positive associations were observed between the number of ideal CVH factors and less decline in the domains of Executive Function and Episodic Memory. Conclusions: The number of ideal CVH metrics was associated with less decline in the domains of Processing Speed and, to a lesser extent, of Executive Function and Episodic Memory. Ideal CVH promotion benefits brain health and cognitive aging.